Entrepreneurial orientation, social embeddedness and non financial performance among Malaysian Indian ethnic entrepreneur in Selangor Klang Valley, Malaysia - Valarmathi, M Subramaniam (2015)
Entrepreneurial orientation (EO) of Malaysian Indian ethnic entrepreneurs and its antecedents and consequences are under-researched. The purpose of present study is to investigate the influence of social embeddedness namely family ties, co-ethnic networks, and mainstream networks on entrepreneurial orientation. The study also examines the non financial performance as consequence of entrepreneurial orientation among Malaysian Indian ethnic entrepreneurs. The data were collected from Malaysian Indian ethnic entrepreneurs in the Selangor, Klang valley, Malaysia. There are 129 questionnaires were used to analyze the data. Results indicate that positive and significant relationship was found between family ties, co-ethnic networks and entrepreneurial orientation. Then, there was no significant relationship between mainstream networks and entrepreneurial orientation. The study also revealed that entrepreneurial orientation has a positive significant influence upon entrepreneur‘s non financial performance. Theoretical and practical implication of the study as well as suggestions for future research was discussed.